2006
DOI: 10.1182/blood.v108.11.3503.3503
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Tumors in Pre-Clinical Models of Multiple Myeloma by Anti-CS1 Monoclonal Antibody HuLuc63: Mechanism of Action Studies.

Abstract: Introduction: We have recently shown that CS1 (CD2 subset 1, CRACC, SLAMF7), a cell surface glycoprotein of the CD2 family, is uniformly expressed on myeloma cells from multiple myeloma (MM) patients. Based on its high expression in MM and limited expression in normal cells, we propose CS1 as a novel and specific antibody target for the treatment of MM. Methods: A panel of monoclonal anti-CS1 antibodies (mAbs) was generated to identify a potential therapeutic candidate. MAb clones MuLuc63 and Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…HuLuc63 also demonstrated dose-dependent ADCC against L363 and OPM2 myeloma cell lines. 17 Accordingly, depletion of NK cells from peripheral blood mononuclear cells and blocking of the Fc receptors (FcR) on NK cells also significantly decreased the anti-tumor effects of HuLuc63 antibody. 14 Van Rhee et al showed that bortezomib pretreatment of myeloma cell line OPM2 led to enhanced dose-dependent ADCC with elotuzumab and this effect was lost after pre-treatment of the effectors with FcR blocking antibodies.…”
Section: Preclinical Development Of Elotuzumabmentioning
confidence: 99%
“…HuLuc63 also demonstrated dose-dependent ADCC against L363 and OPM2 myeloma cell lines. 17 Accordingly, depletion of NK cells from peripheral blood mononuclear cells and blocking of the Fc receptors (FcR) on NK cells also significantly decreased the anti-tumor effects of HuLuc63 antibody. 14 Van Rhee et al showed that bortezomib pretreatment of myeloma cell line OPM2 led to enhanced dose-dependent ADCC with elotuzumab and this effect was lost after pre-treatment of the effectors with FcR blocking antibodies.…”
Section: Preclinical Development Of Elotuzumabmentioning
confidence: 99%
“…MuLuc63 was more potent and showed rapid tumor eradication and was therefore selected for humanization. 39 HuLuc63, the humanized IgG1 version of MuLuc63, later named elotuzumab, exhibited significant antitumor activity in several xenograft models. It is a fully humanized IgG1 mAb and recognizes the extracellular region of human CS1.…”
Section: Targeting Cs1 On Myeloma Cells With Elotuzumab-preclinical Smentioning
confidence: 99%
“…A humanized mAb developed against CS1 elotuzumab (HuLuc63) has been proven to induce significant antimyeloma activity both in vitro and in vivo [ 203 , 205 ]. In vitro , the employment of bortezomib has been shown to increase HuLuc63-induced ADCC [ 206 ]. In vivo injection of the mAb significantly induced tumor regression in xenograft myeloma mouse models [ 203 ].…”
Section: Monoclonal Antibodies In the Treatment Of MMmentioning
confidence: 99%